2016
DOI: 10.1089/ast.2016.1525
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Persistence of Brine on Mars: Experimental Simulations throughout the Diurnal Cycle at the Phoenix Landing Site

Abstract: In the last few years, water ice and salts capable of melting this ice and producing liquid saline water (brine) have been detected on Mars. Moreover, indirect evidence for brine has been found in multiple areas of the planet. Here, we simulate full diurnal cycles of temperature and atmospheric water vapor content at the Phoenix landing site for the first time and show experimentally that, in spite of the low Mars-like chamber temperature, brine forms minutes after the ground temperature exceeds the eutectic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…At the PHX landing site, though, high RH periods during the summer are accompanied by temperatures above the eutectic temperature in the subsurface and are able to potentially generate a liquid phase if magnesium perchlorate is present, even if mixed with mineral soil analogs. These findings are consistent with several other studies on the presence of liquid at the PHX landing site (Cull et al, ; Fischer et al, , ; Zorzano et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At the PHX landing site, though, high RH periods during the summer are accompanied by temperatures above the eutectic temperature in the subsurface and are able to potentially generate a liquid phase if magnesium perchlorate is present, even if mixed with mineral soil analogs. These findings are consistent with several other studies on the presence of liquid at the PHX landing site (Cull et al, ; Fischer et al, , ; Zorzano et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Many recent studies have examined the deliquescence, efflorescence, or freezing of pure perchlorate salts or brines (Fischer et al, , ; Gough et al, ; Nikolakakos & Whiteway, ; Nuding et al, ; Primm et al, ; Toner et al, ). The low‐temperature phase transition behavior of many pure perchlorates is therefore fairly well established.…”
Section: Introductionmentioning
confidence: 99%
“…Confidential manuscript submitted to JGR-Planets tations of liquids at the Phoenix landing site have further been supported by experimental results that suggest a role for deliquescence [Chevrier et al, 2009;Nuding et al, 2014;Fischer et al, 2016].…”
Section: Introductionmentioning
confidence: 70%
“…[21][22][23][24][25] Several laboratory and theoretical studies have investigated the deliquescence and efflorescence of perchlorates at different temperatures. 22,23,[25][26][27][28] For example, a laboratory study by Zorzano et al 23 found that sodium perchlorate could absorb water vapor and form aqueous solutions under Martian conditions at temperatures as low as 225 K. The deliquescence relative humidity (DRH) decreases from 64% at 223 K to 42% at 273 K for Mg(ClO 4 ) 2 $6H 2 O, and decreases from 64% at 228 K to 51% at 273 K for NaClO 4 $H 2 O. 25 The DRH of calcium perchlorate varies between 5% and 55% for the temperature range of 223-273 K, 22 probably because the hydration state of calcium perchlorate changes at different temperatures.…”
Section: Introductionmentioning
confidence: 99%